"Eventually I'm gonna need people": Social capital among college students with developmental disability. (August 2022) - Hoyle, Jessica N.; Laditka, James N.; Laditka, Sarah B.
Abstract: Background and aims: About 18% of college students have disabilities. Social capital, resources we can tap from relationships, may be particularly valuable for students with disabilities. Yet, disabilities often limit the individual's ability to develop or use social capital. We studied how college students with developmental disabilities understand, develop, and use social capital. Methods and procedures: We conducted in-depth semi-structured Zoom interviews with 10 women with developmental disabilities enrolled at a public university in the southeastern United States early in 2021. We examined the qualitative data with thematic analysis. Outcomes and results: Participants averaged age 20; 70% reported attention deficit disorder or attention deficit hyperactivity disorder; 90% reported multiple diagnoses. Most participants described COVID-19 pandemic-related isolation and stress, which magnified both the need for relationships and awareness of that need, prompting participants to become proactive in forming and maintaining relationships despite anxiety about them. Themes were: foundational relationships, reciprocity, expanding horizons, a need for new relationships, focus on the future and relationship barriers. Conclusions and implications: Results highlight the importance of social relationships and the resources they provide to students with disabilities, particularly in stressful times. Colleges can help students by connecting them with others and providing strategies for building and maintaining social capital. What this paper adds: College students with developmental disabilities often face challenges developing and maintaining social capital, resources derived from relationships with other people. These resources are key to success in school and after graduation, as students continue into adulthood. We studied how students with developmental disabilities build social capital. The students described their relationships with others and the types of support they contributed to and received from those relationships. We also extended previous research by examining pandemic-related effects, interviewing participants nearly one year into the COVID-19 pandemic. We provide recommendations for further research and ways colleges and universities can encourage social capital development among all students. Highlights: As many as 18% of college students have a developmental disability. Students with developmental disabilities face barriers to gaining and using social capital. Colleges can help students by providing strategies for social capital formation. Participants described programs promoting social networks and social capital.